2008
DOI: 10.1128/iai.00472-08
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Smallest Structure Capable of Evoking Opsonophagocytic Antibodies against Streptococcus pneumoniae Type 14

Abstract: Synthetic overlapping oligosaccharide fragments ofThe resulting antibodies were then tested for Pn14PS specificity and for their capacity to promote the phagocytosis of S. pneumoniae type 14 bacteria. Earlier studies have reported that the oligosaccharide corresponding to one structural repeating unit of Pn14PS, i.e., Gal-Glc-(Gal-)GlcNAc, induces a specific antibody response to Pn14PS. The broader study described here, which evaluated 16 oligosaccharides, showed that the branched trisaccharide element Glc-(Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
107
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(113 citation statements)
references
References 35 publications
4
107
0
2
Order By: Relevance
“…We found that the fragments with a linear and/or incomplete branched structure did not elicit specific antibodies against native Pn14PS (Fig. 4: JJ118, JJ42, JJ141, DM65, JJ153, JJ9, JJ6 and DM35) [73]. High titer of anti-Pn14PS IgG antibodies was observed when the complete branched structure fragments, conjugated to the protein carrier were used in the mouse model (Fig.…”
mentioning
confidence: 87%
See 4 more Smart Citations
“…We found that the fragments with a linear and/or incomplete branched structure did not elicit specific antibodies against native Pn14PS (Fig. 4: JJ118, JJ42, JJ141, DM65, JJ153, JJ9, JJ6 and DM35) [73]. High titer of anti-Pn14PS IgG antibodies was observed when the complete branched structure fragments, conjugated to the protein carrier were used in the mouse model (Fig.…”
mentioning
confidence: 87%
“…Antibody titers were expressed as the log10 of the dilution Filled circle = glucose (Glc); open circle = galactose (Gal), and filled square = N-acetylglucosamine (GlcNAc). In conclusion, the present study has shown that the branched trisaccharide Glc-(Gal-)GlcNAc is the core structure inducing Pn14PS-specific antibodies and that the neighboring galactose at the non-reducing end significantly contributes to the induction of phagocytosispromoting antibodies [73]. Our study provides evidence that the branched tetrasaccharide Gal-Glc-(Gal-)GlcNAc is a prime candidate for a synthetic oligosaccharide conjugate vaccine against infections caused by S. pneumoniae type 14 [73].…”
mentioning
confidence: 89%
See 3 more Smart Citations